In the Shadow of the Volcano: the Etna Region in the modern Period - Emanuela Garofalo (Agathón)
Among the many manifestations of the relationship between architecture and nature, a particularly significant case study is that of volcanic territories, both in terms of their implications for aesthetic research and visual considerations, and for the construction and material composition of the buildings realized out in these contexts. The fascination aroused by volcanic eruptions throughout the centuries certainly contributed to the persistence of myths and the development of a collective imaginary, resulting in the construction of local identities that are deep-rooted in the strong character of the territory itself, with significant effects in the architectural sphere as well. The aim of this article is to analyze architectural works built in the area of Etna during the early modern period by weaving together data drawn from archival and iconographical sources and the direct observation of select architectural case studies. The focus is on conditioning and opportunities coming from their setting in the shadow of the volcano.